THE EVOLUTION OF URDU LANGUAGE: HISTORICAL PERSPECTIVES AND MODERN IMPLICATIONS - بہار احمد (RADJA PUBLIKA, 2024)
Urdu, an Indo-Aryan language, has evolved over centuries through a complex interplay of linguistic, cultural, and political influences. This paper traces the historical development of Urdu from its origins in the Delhi Sultanate to its golden era under the Mughals, and through the colonial period to its contemporary status. The linguistic characteristics, including its phonetics, morphology, and vocabulary, are examined to understand the richness of the language. The paper also explores the script and orthography, highlighting the aesthetic beauty of Urdu calligraphy. Furthermore, the cultural significance of Urdu literature and its prominent literary figures are discussed. In the modern context, the paper addresses the challenges Urdu faces, such as declining usage and technological barriers, and explores the opportunities for its preservation and promotion. Through this comprehensive study, the paper underscores the enduring relevance and cultural importance of Urdu in the South Asian context.